Of Beavers and Tables: The Role of Animacy in the Processing of Grammatical Gender Within a Picture-Word Interference Task - Sá-Leite, Ana Rita; Haro, Juan; Comesaña, Montserrat; Fraga, Isabel (Frontiers in Psychology, 2021)
Grammatical gender processing during language production has classically been studied using the so-called picture-word interference (PWI) task. In this procedure, participants are presented with pictures they must name using target nouns while ignoring superimposed written distractor nouns. Variations in response times are expected depending on the congruency between the gender values of targets and distractors. However, there have been disparate results in terms of the mandatory character of an agreement context to observe competitive gender effects and the interpretation of the direction of these effects in Romance languages, this probably due to uncontrolled variables such as animacy. In the present study, we conducted two PWI experiments with European Portuguese speakers who were asked to produce bare nouns. The percentage of animate targets within the list was manipulated: 0%, 25%, 50% and 100%. A gender congruency effect was found restricted to the 0% list (all targets were inanimate). Results support the selection of gender in transparent languages in the absence of an agreement context, as predicted by the Gender Acquisition and Processing (GAP) hypothesis (Sá-Leite et al., 2019), and are interpreted through the attentional mechanisms involved in the PWI paradigm, in which the processing of animate targets would be favoured to the detriment of distractors due to biological relevance and semantic prioritization.